Development of an advanced semi-active damper using smart fluid - Ferdaus, Mohammad Meftahul; Rashid, Muhammad Mahbubur; Bhuiyan, Moinul (2013)
In this paper an advanced semi-active damper is designed and experimentally studied to investigate and establish its behavior. A prototype Magneto-rheological fluid Damper is designed as advanced semi-active damper due to its huge advantages. Magneto-rheological fluid with improved dispersion stability is prepared here as smart fluid. The relation between force and displacement for various current has been established to develop the semi-active damper model. In this study a fuzzy tuned PID controller is opted to achieve better response for a various frequency input. The proposed MR damper can be applied to vehicle syspension system and other suspension mitigation system widely. Moreover, the identified behaviour can help in further development of MR damper technology. The characteristics obtained from of MR damper is more realistic as it is obtained from experiments.